Penggunaan Dampak Positif Terhadap Eksplorasi Kreativitas Literasi Digital Painting Canva Pembelajaran Puisi Kelas 5 SDN Gondek - Widiarti, Melia; Laksono, Kisyani; Amri, Miftachul (Cetta: Jurnal Ilmu Pendidikan, 2024)
This study aims to examine the use of Canva's digital painting platform in poetry learning for grade 5 students of SDN Gondek. The research methods used were observation, interviews, and document analysis to collect data related to the exploration of Canva's digital painting literacy creativity in poetry learning. The results showed that the use of Canva positively influenced students' exploration of creativity in understanding and expressing poetry. Students show great interest and enthusiasm in using Canva to illustrate their understanding of the poetry being studied. Thus, the use of technology in digital painting literacy can increase students' creativity in learning poetry at the elementary level.